(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Series-wound DC motors remain attractive in many applications due to their simplicity, robustness, and cost-effectiveness. However, their performance and service life depend heavily on effective thermal management. This study presents a detailed investigation into the modeling, simulation, experimental validation, and thermal analysis of a series-wound DC motor under various cooling strategies. A thermal circuit model was developed in LabVIEW to predict temperature rise in different motor components, while a custom experimental setup was constructed to directly measure torque, current, and temperature during real-world operation. Multiple thermocouples were embedded in the motor to capture temperature distributions with high accuracy, and LabVIEW was employed for precise data acquisition and processing. Experimental results were used to refine and assess the thermal model, enabling a comparison between solid and optimized motor configurations. The findings highlight the impact of selecting appropriate cooling techniques on reducing hot-spot temperatures, thereby improving overall motor efficiency, reliability, and lifespan.